The relationship between customer satisfaction and service quality towards TM global products at Petaling Jaya / Nor Hasidah Hashim - Hashim, Nor Hasidah (Faculty of Business and Management, 2011)
Purpose – The purpose of this study is to identify the factors customer satisfaction towards global products.